Biological Aspects of Popular Culture - Danesi, Marcel (Recherches sémiotiques / Semiotic Inquiry, 2019)
There are various theories for the origins and rise of popular culture, ranging from sociological to political-ideological ones. But given the existence of such forms of culture across cultural spaces and time, they hardly penetrate the raison d’être of such forms of human expression. Perhaps the one that comes closest to explaining the universality popular and populist forms of culture was put forward by Mikhail Bakhtin, who claimed that spectacles such as carnivals and texts such as novels are popular because they tap into a psychic need, allowing bodily needs and experiences to gain expression and validation. This paper will explore this idea from a generic biosemiotic perspective, looking at how pop culture is a modern-day expressive version of this need.